Physical activity policy implementation and physical activity levels in the European Union: Are we on track to close the gap between policy and practice? - Whiting, Stephen; Abu-Omar, Karim; Gelius, Peter; Firmino-Machado, João; Rakovac, Ivo; Mendes, Romeu (Health policy (Amsterdam, Netherlands), 2025)
National policies are a key starting point to achieve changes in population health. This study aimed to provide an overview of the relationship between physical activity policy implementation and the levels of sufficient physical activity across the European Union over the last decade. Data from the 23 indicators of the European Union Health-Enhancing Physical Activity Monitoring Framework established to monitor country implementation of the European Union Physical Activity Guidelines from 2015, 2018 and 2021, and physical activity prevalence data from the Special Eurobarometer on Sport and Physical Activity in 2013, 2017 and 2022 were analysed. European Union Member States significantly increased their physical activity policy implementation from 2015 to 2021 by 13.2 % (63.30 ± 18.89 versus 76.51 ± 14.94 %, p < 0.001, 95 % CI [-19.97, -6.45]). However, no significant change in levels of sufficient physical activity was found between 2013 and 2022 (60.59 ± 15.67 versus 61.70 ± 17.67 %, p = 0.360, 95 % CI [-3.61, 1.39]). Additionally, most European Union countries are not on track to meet the targeted 10 % relative reduction in levels of insufficient physical activity by 2025. Physical activity policies in the European Union do not appear to be related with the intended goal of increasing levels of physical activity. Policies may need to be reviewed and policy monitoring expanded, strengthened, and better integrated.
CRIS-Team Scopus Importer:2024-11-22
Keywords: European Union; Health policy; Physical activity; Physical inactivity; Policy implementation